ENHANCING STUDENTS’ ARTISTIC SKILLS THROUGH COMPETENCY-BASED AND INTERACTIVE VISUAL ARTS EDUCATION - Boboniyozova Roziya Mirsalim qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores how competency-based and interactive pedagogical approaches enhance students’ artistic skills in visual arts education. Emphasis is placed on methods such as project-based learning, flipped classroom, and collaborative exercises, which foster creativity, critical thinking, and independent problem-solving. Drawing upon the research of Shovdirov S.A. and other scholars, the article demonstrates how modern pedagogical strategies improve artistic literacy, aesthetic appreciation, and overall engagement, preparing students for both practical and theoretical challenges in art education.